Unique Christian Therapeutic Counseling: Maximizing Results and Shortening Time - Royal Evendi Purba; Junifrius Gultom (Bisma The Journal of Counseling, 2022)
This article describes Christian therapeutic counseling that can help make the counseling process effective. The purpose of Christian therapeutic counseling is not only to want someone to experience recovery from the problem, but above all, the result of the counseling is that the counselee experiences the likeness of Christ who healed him. To get to that stage, one must start with a change in life because one has been freed, freed, recovered, and has personally met God and experienced the likeness of Christ. This can be called unique counseling, maximizing results and shortening time. The research method used is descriptive qualitative. The study's results stated that Therapeutic counseling impacts the process of believers becoming in the image and likeness of God.  Counselors must synergize with other fields with different gifts, including the local Church, discipleship team, mission, and pastoral because synergy helps perfect a counselee's recovery and shorten the time.